Design of a Array Micro-Lenses Silicon Photovoltaic Cell - Bhardwaj, Vikash; Tyagi, Anuradha (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
In this paper, another model for exhibit of smaller scale lenses concentrator was outlined. This concentrator comprises of exhibit of smaller scale lenses (MLA) to center sunlight based light on four rectangular slaps of photovoltaic Si sun based cell. The outline mean to diminish the expense of the concentrators by decreases the powerful range of the high cost silicon material region and rearranged the structure of the framework. The sunlight based cell with the MLA-concentrator includes vitality change productivity (11.98%) and decreasing the aggregate expense